Review of Islamic Law on the Distribution of Inheritance in Muslim Families - Habib, Muhammad; Pratama, Risky Eka; Kurniawan, Jonathan James; Saputro, Muhammad Susilo Agung; Prianto, Asep; Yarmanto, Yarmanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to study how methods for dividing inheritance assets based on Islamic Inheritance Law and the Compilation of Islamic Law are able to resolve requests or disputes over the distribution of inheritance assets between Muslim people. This research uses a literature study method by collecting data from various sources, such as books, journal articles and previous research results. then analyzed using a qualitative descriptive method which is a logical and systematic legal argumentation. This research aims to provide a deeper understanding of how Islamic law influences inheritance distribution practices in Muslim families, as well as providing a framework for understanding how Islamic law can be adapted in the context of civil law to achieve better justice for all parties involved.